Control and optimization methods for electric smart grids - Ilic, Marija D.; Chakrabortty, Aranya (Power Electronics and Power Systems, 2012)
Control and Optimization Methods for Electric Smart Grids brings together leading experts in power, control and communication systems,and consolidates some of the most promising recent research in smart grid modeling,control and optimization in hopes of laying the foundation for future advances in this critical field of study. The contents comprise eighteen essays addressing wide varieties of control-theoretic problems for tomorrow's power grid. Topics covered include: Control architectures for power system networks with large-scale penetration of renewable energy and plug-in vehicles Optimal demand response New modeling methods for electricity markets Control strategies for data centers Cyber-security Wide-area monitoring and control using synchronized phasor measurements. The authors present theoretical results supported by illustrative examples and practical case studies, making the material comprehensible to a wide audience. The results reflect the exponential transformation that today's grid is going through in terms of design and operation, and provide a vision of how control theorists can contribute to this enterprise of making tomorrow's cyber-integrated energy infrastructure a reality. Control and Optimization Methods for Electric Smart Grids has a broad scope, making it an ideal resource for graduate students in power and control systems. The work will also be of practical interest to researchers, engineers and power system operators seeking to understand how relevant methods of control and optimization can be used for operating the grid smartly.